Theoretical Aspects of Security Concept Transformation - Cvetkovski, Sergej; Spasov, Nikolco; Pavleski, Aleksandar (Faculty of Philosophy, 2020)
Safety and security are top priorities in our society and addressing problems in these areas is crucial. Several different kinds of safety or security exist today, such as interna tional security, cyber security, physical security, fire safety, and so on. The scientific community is starting to address the creation of a theory of safety and security. The theory of safety and security will be followed by a series of default theories. This paper discusses the concepts and theoretical sources we can draw from for the theory of safety and security, as well as subsequent knowledge. Nowadays, a mostly pragmatic approach prevails in the safety and security research. Until now, there is no common theoretical basis for safety or security.
Keywords: theory of safety and security; concept; risk theory; crisis theory; causality